Health‐related quality of life improves 1 year after parathyroidectomy in primary hyperparathyroidism: A prospective cohort study. (22nd October 2018) - Ejlsmark‐Svensson, Henriette; Sikjaer, Tanja; Webb, Susan M.; Rejnmark, Lars; Rolighed, Lars
Abstract: Objective: Impaired quality of life (QoL) in primary hyperparathyroidism (PHPT) is commonly present. Patients may complain about nonspecific neurocognitive symptoms which can be difficult to quantify. Two different disease‐specific questionnaires have been developed, that is, the parathyroid assessment of symptoms score (PAS) and the primary hyperparathyroidism quality of life (PHPQoL). Using these two questionnaires, we assessed relationship between QoL and biochemical indices in PHPT and effects of parathyroidectomy (PTX). Design: A prospective cohort study. Methods: Patients with PHPT diagnosed from 2015 to 2017 were asked to answer the questionnaires before and 12 months after PTX. Biochemistry was obtained on both occasions. Results: A total of 104 PHPT patients answered PAS and PHPQoL questionnaires at baseline, with a median age of 64 years (73% females). PHPQoL score correlated inversely with ionized calcium and PTH at baseline ( P  ˂ 0.04). Total PAS and PHPQoL score did not differ between those with and without osteoporosis, renal calcifications and impaired renal function. Based on levels of ionized calcium, PHPQoL differed significantly between patients with mild‐ and moderate‐severe hypercalcemia ( P  = 0.01). Fifty‐three patients answered PAS and PHPQoL 12 months after PTX showing an improved QoL at follow‐up ( P all  ˂ 0.02). Stratifying patients into groups based on levels of ionized calcium showed a significantly improved PHPQoL score in patients with mild (˂1.45 mmol/L) as well as moderate‐severe hypercalcemia (≥1.45 mmol/L) at follow‐up ( P all  ˂ 0.03). Conclusion: Quality of life improved 12 months after PTX in PHPT patients. Impaired QoL seems to be associated with the degree of hypercalcemia rather than organ manifestations attributable to PHPT.